ผลกระทบของนโยบายการขอต่อใบอนุญาตประกอบวิชาชีพครูที่มีต่อครูและนักเรียน : การวิจัยแบบผสม - สิริวรรณ มีรอด (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of this mixed-method study were to (1) preliminarily analyze the acceptance of the teachers’ license renewal policy; (2) analyze teachers’ participation in activities organized by the Teacher’s Council of Thailand and compare the participation of teachers with different backgrounds; (3) analyze the impact of the policy on the teachers’ performance, their teaching management and their quality of life; (4) analyze the impact of the policy on the students to find out whether their teachers were competent, their teaching management was adequate and their teaching methods were current. The tools were a questionnaire and an interview form. The collection of the data was divided into two steps. The first step was the collection of the quantitative data. The sample included 560 teachers and 417 students from both public and private schools in Ayutthaya province. The second step was the collection of the qualitative data. The sample included 15 teachers in Ayutthaya province. The data were analyzed with descriptive statistics which were percentage, mean and standard deviation and comparative statistics ANOVA. It was found that; 1.As for the teachers’ acceptance of activities concerning the license renewal, taking courses related to the job descriptions came first, followed by attending lectures, discussions, workshops, seminars and other training where participants received a certificate of attendance and taking an educational visit respectively. The criteria for the renewal which teachers agreed to most were (1) the license was essential for being a teacher, (2) the Council should disseminate the criteria to the teachers throughout the country and (3) abiding by the teachers’ codes of conduct is necessary for the renewal. 2. In general, participation in activities required by the Council was at the high level. Most teachers participated in taking training sessions and received a certificate issued by the Council. This certificate recognized their expertise as a teacher. They also participated in writing a report or organizing an activity which supported learning management and taking courses which were related to their jobs. 3.As for the impact on teachers, most teachers agreed that the policy affected advancement in their career path; as a result, they had to organize the most effective learning activities, but in terms of their quality of life, the policy caused the teachers to be bored with the assessing criteria. 4.As for the impact on students, the teachers’ participation in activities organized by the Council was related to the teachers’ teaching-learning management according to the students’ perceptions. The teachers’ participation in developing their work and profession affected the teachers’ classroom management. The teachers who participated in professional development tended to manage the teaching-leaning activities better than those who did not according to the students’ perceptions.